2020
DOI: 10.3168/jds.2019-17854
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the spray-drying treatment to inactivate the bovine leukemia virus in bovine colostrum

Abstract: Previous studies have shown the presence of bovine leukemia virus (BLV) in colostrum and milk of naturally infected cows. The relationship between virus or provirus and specific antibodies in these secretions is particular to each infected cow and will probably determine whether the consumption of colostrum or milk from these naturally infected dams provides an infective or a protective effect in recipient calves. Our recent findings suggest that this issue is a key point in BLV transmission in very young calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Moreover, our group has recently reported that the experimental spray-drying process is effective in inactivating infectious BLV in colostrum. In that study, we inoculated susceptible lambs with treated (spry-dried) or untreated colostrum spiked with BLV-infected cells and found that lambs that had received the untreated colostrum showed evidence of infection 60 days post-inoculation ( 75 ).…”
Section: Preventive Strategies When Feeding Calves With Colostrum Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our group has recently reported that the experimental spray-drying process is effective in inactivating infectious BLV in colostrum. In that study, we inoculated susceptible lambs with treated (spry-dried) or untreated colostrum spiked with BLV-infected cells and found that lambs that had received the untreated colostrum showed evidence of infection 60 days post-inoculation ( 75 ).…”
Section: Preventive Strategies When Feeding Calves With Colostrum Andmentioning
confidence: 99%
“…Pasteurization of milk is another feasible strategy to ensure the inactivation of BLV without significantly altering the concentration of immunoglobulins or their physiological activities ( 75 – 77 ). It has been reported that sheep inoculated with milk experimentally contaminated with BLV and treated by a simulated high-temperature short-time (HT ST) pasteurization procedure do not become infected or develop tumors ( 75 , 77 ). In addition, HT ST pasteurization has the additional benefit of helping to limit the spread of Johne's disease and other pathogens ( 78 ).…”
Section: Preventive Strategies When Feeding Calves With Colostrum Andmentioning
confidence: 99%
“…Lactoferrin is lost throughout a temperature range of 65–95 °C as time and temperature increase [ 45 ]. Additionally, spray drying is efficient in suppressing the transmission of the bovine leukemia virus (BLV) in milk and colostrum to some extent [ 46 ].…”
Section: Impact Of Processing Techniques and Conditions On Colostrum ...mentioning
confidence: 99%
“…However, bovine colostrum may be contaminated with pathogens, including rotavirus, Cryptosporidium , bovine leukosis virus or Mycobacterium avium subsp. paratuberculosis , thus posing an infection risk 12–15 …”
Section: Introductionmentioning
confidence: 99%
“…paratuberculosis, thus posing an infection risk. [12][13][14][15] Colostrum replacers are synthetic feed products designed to completely replace maternal colostrum. 16 However, few studies have analysed the impact of feeding colostrum replacers to lambs.…”
Section: Introductionmentioning
confidence: 99%